2008
DOI: 10.1183/09031936.00166907
|View full text |Cite
|
Sign up to set email alerts
|

The epidermal growth factor receptor mediates allergic airway remodelling in the rat

Abstract: The chronicity of bronchial asthma is attributed to persistent airway inflammation and to a variety of structural changes, or remodelling, that includes smooth muscle and goblet cell hyperplasia.To investigate the mechanisms of airway remodelling, the current authors used an established allergen (ovalbumin; OVA)-driven rodent model (the Brown Norway rat).Brown Norway rats were sensitised to OVA and challenged three times at 5-day intervals to evoke airway remodelling. The effects of an epidermal growth factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
91
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 45 publications
(94 reference statements)
3
91
0
Order By: Relevance
“…Human asthmatic airways show increased EGFR immunoreactivity in airway epithelium, glands, and smooth muscle [5] and EGFR activation has been reported to promote epithelial repair and to induce mucin production and remodeling of airway tissues [6,7]. We previously reported that multiple OVA challenges increased protein expression of the EGFR ligand, heparin-binding EGF-like growth factor (HB-EGF) in airway epithelium in Brown Norway (BN) rats [4]. The inhibition of the tyrosine kinase signaling cascade might have therapeutic effects in asthma [8].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Human asthmatic airways show increased EGFR immunoreactivity in airway epithelium, glands, and smooth muscle [5] and EGFR activation has been reported to promote epithelial repair and to induce mucin production and remodeling of airway tissues [6,7]. We previously reported that multiple OVA challenges increased protein expression of the EGFR ligand, heparin-binding EGF-like growth factor (HB-EGF) in airway epithelium in Brown Norway (BN) rats [4]. The inhibition of the tyrosine kinase signaling cascade might have therapeutic effects in asthma [8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication has suggested a role for amphiregulin, an EGFR ligand, in Th2-cell differentiation in the mouse [15]. Therefore, it is possible that EGFR signaling may be important during the sensitization phase of the immune response to allergen and may affect airway inflammation and airway responsiveness by altering the function of immune cells including lymphocytes.The BN rat model of asthma has been widely used [4,16] as it develops high levels of IgE upon sensitization [17] and has typical Th2 inflammation, early-and late-phase airway responses and AHR after allergen challenge [18]. In the current study, we hypothesized that the inhibition of EGFR signaling by the selective EGFR-TK inhibitor AG1478 given at the time of allergic sensitization was capable of modulating immune reactions in the BN rat.…”
mentioning
confidence: 95%
See 3 more Smart Citations